Penggunaan Metode Seven New Quality Tools dan Metode DMAIC Six Sigma Pada Penerapan Pengendalian Kualitas Produk - Yurin Febria Suci; Yuki Novia Nasution; Nanda Arista Rizki (EKSPONENSIAL, 2017)
Product quality control is a technique and activities or planned actions undertaken to achieve, maintain, and improve the quality of products and services to meet with customers standards and satisfaction. This study aim to address the product quality at a company using statistical methods of products control. The methods are Seven New Quality Tools and DMAIC Six Sigma which are used on a product with a brand of Roti Durian Panglima, produced by PT. Panglima Roqiiqu Group in June 2016. Based on the result by using Seven New Quality Tools method, there are five factors that caused defect on Roti Durian Panglima product, which are : human factor, materials, environmental, machine, and work method, which makes the priority of the product improvement lays on human factor. Meanwhile, the use of DMAIC Six Sigma method has obtained performance baseline values at 4,48 Sigma with four kinds of defects on Roti Durian Panglima products, and based on improvement phase using PFMEA method, the priority on product improvement also lays on human factor.